(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the proportion of high school students with accurate knowledge and practices regarding Dengue fever prevention, and associated factors, in Phong Dien district, Can Tho city. Research methods: A cross-sectional analytical descriptive study was conducted on 220 students from September to November 2024. Results: The survey of 220 students, 90.9% of students had correct knowledge of Dengue fever, and only 66.8% of students had correct practice. Male students have correct knowledge and correct practice at rates of 81.3% and 53.1%, respectively, lower than female students with rates of correct knowledge at 94.9% and correct practice at 72.4%, with OR = 4.26, respectively; 95%CI (1.49-12.66) and OR = 2.31; 95%CI (1.20-4.42) and all have p < 0.001. Similarly, students with good academic performance or higher have a higher rate of correct practice than the other group with rates of 79.7% and 60.9%, respectively, with OR = 2.51 and 95%CI (1.24-5.33). Factors that are not related to correct knowledge and practice are grade level and number of family members. Conclusions: The rates of correct knowledge and practices regarding Dengue fever prevention among high school students in Phong Dien district were 90.9% and 66.8%, respectively. Factors such as female gender and good academic performance were associated with better knowledge and practices.